Human Resource Management Paradigm Based on Kalimantan’s Local Wisdom - Eva Pronica (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to formulate a new paradigm of human resource management (HRM) based on Kalimantan’s local wisdom within the framework of national HRM. Employing a sequential explanatory mixed methods design, quantitative data were collected through surveys of 300–400 respondents, while qualitative data were obtained from in depth interviews with traditional leaders, civil servants, and local organizational leaders. Data analysis utilized SEM PLS to test latent variable relationships, NVivo for thematic coding, and Grounded Theory to develop new theoretical insights. Findings reveal that competence, adaptive resilience, productive mobility, and cultural integration are the core pillars of HRM. Cultural values such as community cooperation (gotong royong), consensus building (musyawarah), and collaborative leadership significantly strengthen social adaptation and organizational integration. Validity and reliability tests (CFA, Cronbach’s Alpha, and data triangulation) confirm the robustness of the research instruments. This study extends global HRM theories by introducing a new dimension localized HRM paradigm which positions local wisdom as a strategic variable in the development of Nusantara Capital City (IKN) and the national HRM framework.